Sustained NMDA receptor hypofunction impairs brain-derived neurotropic factor signalling in the PFC, but not in the hippocampus, and disturbs PFC-dependent cognition in mice - Tanqueiro, Sara (2021)
Copyright © 2021, © SAGE Publications